Author’s Onomasticon of Olena Ryzhko: a Case Study of Stories for Young Adults (Linguostylistic Studies, 2021)
Linguistic studies of the language units and their functioning features in literary texts, combined with the literary analysis of the text poetics, provide a comprehensive and multifaceted perception of them. In the context of reviewing literature addressed to young adults, the issue of adult writers’ ability to communicate with the teenaged recipient through the text is of particular importance. The plot, the characters, and the language of the work are the basis of such communication. In the artistic and figurative content of the text, an onomasticon is a tool for expressing the characteristic features and bringing the characters closer to the reader, and also a particular element of the author's style. A striking example of the author’s onomasticon is the system of anthroponyms in the novels addressed to teenagers of the modern Ukrainian writer Olena Ryzhko. The system components – names, diminutive-affectionate forms of names, surnames, bynames, and nicknames of characters – are the subject matter of the analysis presented in the article. With the stylistic features of the author's writing in view, due not only to the laws of the art of speech but also the specifics of the addressee, we distinguish several models of presentating onyms in her works for young readers: use of proper names or nicknames in the title of a story; revealing the etymology of anthroponyms in the process of introducing new characters into the plot; actualization of nicknames, diminutive-affectionate and abbreviated forms of names with or without the parallel submission by their canonized forms; priority given to nicknames and gender-ambiguous onyms.The classification of onyms and their analysis allows concluding that in the story Girl from the City, teenagers are endowed with traditional names used in several versions and nicknames, formed from surnames or names. Nicknames dominate in the story Only Maru Knows. Nicknames and gender-ambiguous onyms predominate in the story Mousetrap. Here the author demonstrates the logic of teenagers to choose a nickname for social networks. Diminutive-affectionate forms of names are actively used in the detective story King of the Darknet and abbreviated forms of names, reminiscent of bynames and nicknames, in the story Stung by Betrayal. As the analysis showed, all of them carry a stylistic loading and perform the function of characterizing the hero. The etymology and semantics of the name emphasize its external and psychological portrait. O. Ryzhko often comments on and details the origin and perception of her characters’ nicknames and names, often the perception of nicknames by teenagers themselves, which strengthens the scientific interest in onomasticon of her works.
Keywords: anthroponyms; bynames; nicknames; literature for young adults